North woods - Mason, Daniel 1976- (John Murray, 2023)
"When a pair of young lovers abscond from a Puritan colony, little do they know that their humble cabin in the woods will become the home of an extraordinary succession of human and inhuman characters alike. An English soldier, destined for glory, abandons the battlefields of the New World to devote himself to apples. A pair of spinster twins navigate war and famine, envy and desire. A crime reporter unearths a mass grave - only to discover that the ancient trees refuse to give up their secrets. A lovelorn painter, a sinister conman, a stalking panther, a lusty beetle: as each inhabitant confronts the wonder and mystery around them, they begin to realize that the dark, raucous, beautiful past is very much alive."--Publisher
Keywords: Dwellings / New England / History / Fiction; Forests and forestry / New England / Fiction; Human beings / Effect of environment on / Fiction; New England / Social life and customs / Fiction; Êtres humains / Influence de l'environnement / Romans, nouvelles, etc; Nouvelle-Angleterre / Murs et coutumes / Romans, nouvelles, etc; Dwellings; Forests and forestry; Human beings / Effect of environment on; Manners and customs; New England; Fiction; Historical fiction; History; Nature fiction; Pastoral fiction; Romans pastoraux